Hotel’s Sustainable Business Strategy During and Post COVID-19 Pandemic : A case study at Hotel Grage Resort Sangkan, Kuningan, Indonesia - Awaluddin, Robi; Surgawati, Iis (Journal of Research on Business and Tourism, 2024)
The COVID-19 pandemic has had a significant impact on the hospitality industry, especially the Grage Resort Sangkan hotel in Kuningan Regency, which has had a decreased occupancy rate of up to 50 percent. This study aims to map the sustainable strategies implemented by the Grage Resort Sangkan hotel in Kuningan Regency during and after the Covid-19 pandemic. The qualitative method used in this study is a research method used with in-depth interview on stakeholders related to four aspects of management: marketing, production, human resource, and financing, also with the 9-elements business model canvas mapping approach including customer segments, value propositions, channels, revenue streams, key resources, customer relationships, key activities, key partnerships, and cost structure. The results of the study show that, when a pandemic occurs, the strategy taken is to lay off contract workers and work from home for permanent employees, change marketing strategies from offline to focusing on digital marketing, sell vouchers that are valid for up to one year. Meanwhile, moving further into the COVID-19 pandemic, hotels continue to use digital marketing strategies and continue to maintain health protocols, provide discount vouchers until stable income returns sustainably.